Telework preference: an understanding from theory of planned behavior - Leiva, Pedro I.; Kausel, Edgar E.; Madrid, Hector P.; Alday, Rodrigo A. (Frontiers in Organizational Psychology, 2025)
IntroductionThe massive implementation of teleworking during the COVID-19 pandemic highlighted its advantages for employees and organizations. Afterwards, transitioning back to the office, some companies are considering hybrid arrangements to sustain the positive effects of teleworking on job performance. This study, performed during the COVID-19 pandemic, argues that effective telework depends not only on organizational support but also on employees' preferences for telework.ObjectiveThe purpose of the study was to examine predictors of employee telework preference. Drawing on the Theory of Planned Behavior (TPB), we propose that employees' telework preference is influenced by their attitudes and subjective norms regarding teleworking, moderated by their perceptions of telework behavioral control.MethodsData was collected with a two-wave survey from 162 employees of two service organizations in Chile, South America.ResultsOur findings reveal that positive attitudes toward teleworking significantly predict telework preference. Additionally, the subjective norm positively influences telework preference when employees perceive high behavioral control.ConclusionThese findings contribute to TPB and telework management literature broadening the scope of TPB on telework and offering practical insights for enhancing telework management.